2011
DOI: 10.3892/or.2011.1529
|View full text |Cite
|
Sign up to set email alerts
|

PI-PLCβ1 gene copy number alterations in breast cancer

Abstract: Abstract. Deregulation of signal transduction pathways frequently confers selective biological advantages to tumors. Phosphoinositides play an essential role in numerous cellular functions and, among the enzymes implicated in these processes, phosphoinositide-specific phospholipase C β1 (PI-PLCβ1) is one of the key regulators. In the present study, a fluorescence in situ hybridization (FISH) approach was used to investigate PI-PLCβ1 gene copy number alterations in various types of breast cancer differing in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“… 21 In breast cancer, gain of PLCB1 closely related to histological grade and proliferative index, and low expression of PLCB1 in luminal-like A type tumors which had a relatively good prognosis. 16 An earlier study found that a role for gains on chromosomes 8q and 20 as predictors of poor outcome in hepatoblastomas. 22 The PLCB1 gene is located at chromosome 20p12, which makes us concern its up-regulated status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 21 In breast cancer, gain of PLCB1 closely related to histological grade and proliferative index, and low expression of PLCB1 in luminal-like A type tumors which had a relatively good prognosis. 16 An earlier study found that a role for gains on chromosomes 8q and 20 as predictors of poor outcome in hepatoblastomas. 22 The PLCB1 gene is located at chromosome 20p12, which makes us concern its up-regulated status.…”
Section: Discussionmentioning
confidence: 99%
“… 14 More importantly, elevated level of PLCB1 in carcinogenesis has also been recently reported. 15 Molinari et al 16 demonstrated that PLCB1 gene copy number altered in breast cancer and the overexpression of PLCB1 was associated with histological grade and proliferative index.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is possible that signaling from GPCRs could confer survival benefits for cells expressing high levels of PLCB1. The high expression of PLCB1 was also shown to be related to the development and poor prognosis of various cancers, including hepatocarcinoma [ 43 , 44 , 45 ], colorectal cancers [ 46 , 47 ], non-small cell lung carcinoma [ 45 ], breast cancer [ 48 ], and acute myeloid leukemia [ 49 ], suggesting its oncogenic role in different cancers.…”
Section: Discussionmentioning
confidence: 99%
“… 13 β-actin was used as normalizing gene. 14 The amplification conditions were 95 °C for 3 min, 35 cycles of 95 °C for 30 s, 60 °C for 30 s, and 72 °C for 30 s. The amplicons were separated and visualized on a 2% agarose gel stained with ethidium bromide.…”
Section: Methodsmentioning
confidence: 99%